Active Elbow Orthosis. (8th September 2014) - Ripel, Tomas; Krejsa, Jiri; Hrbacek, Jan; Cizmar, Igor
This paper presents a novel approach to the design of a motorized rehabilitation device – active elbow orthosis (AEO) – inspired by the principles of robotic exoskeletons. The device is currently designed for the elbow joint, but can be easily modified for other joints as well. AEO determines the motion activity of the patient using a strain gauge and utilizes this measurement to control the actuator that drives the forearm part of the orthosis. Patient activity level is related to a free arm measurement obtained via a calibration procedure prior to the exercise. A high-level control module offers several types of exercises mimicking the physiotherapist. The device was successfully verified by tests on a number of patients, resulting in extended range of elbow-joint motion.